EFEKTIVITAS PENAGIHAN PAJAK DENGAN SURAT TEGURAN, SURAT PAKSA DAN PENYITAAN DALAM MENGOPTIMALKAN PENERIMAAN PAJAK DI KANTOR PELAYANAN PAJAK PRATAMA MALANG SELATAN - Destriyatna, Gilang (Jurnal Mahasiswa Perpajakan, 2014)
National revenue from tax sector in recent years is not reaching the target. The government has attempted some measures to maximize tax revenue. One of them is to collect the tax debt from tax payer. Based on Act No. 19 of 2000 about Tax Collection with Letter of Compulsion, tax debt is a base to collet the tax. The objective of research is to understand the effectiveness rate and the contribution rate of tax collection through reprimand letter, compulsion letter and confiscation letter in order to liquidate tax debt. Research method is qualitative. Data analysis tool is using Miles & Huberman’s Data Interactive Model (1984) which includes Data Reduction, Data Display and Conclusion & Verification. Result of data analysis indicates that the effectiveness rate of tax collection with Reprimend Letter is not effective, that Compulsion Letter is quite effective, and Confiscation Letter is not effective. The contribution of tax revenue from tax collection with Reprimand Letter, Compulsion Letter and Confiscation Letter to optimize tax revenue at Tax Office of Pratama in South Malang therefore is very low. Keywords: Tax Debt, SKP, Tax Collection, Compulsion Letter